2021
DOI: 10.1016/j.tmaid.2021.101997
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the coronavirus disease 2019 epidemic on notifiable infectious diseases in Taiwan: A database analysis

Abstract: Introduction The impact of the COVID-19 pandemic on the incidence of notifiable infectious diseases (NIDs) in Taiwan remains unclear. Materials and Methods The number of cases of NID (n = 42) between January and September 2019 and 2020 were obtained from the open database from Taiwan Centers for Disease Control. Results The number of NID cases was 21,895 between January and September 2020, which was lower than the number of cases during the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 35 publications
13
28
0
2
Order By: Relevance
“…The decrease in the number of LGV cases during the strict lockdown is in agreement with other studies [ 5 ]. This outcome was probably related to the Spanish government’s decision to minimise all healthcare activities that were not dedicated to COVID-19 in primary care centres, such as STI clinics.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decrease in the number of LGV cases during the strict lockdown is in agreement with other studies [ 5 ]. This outcome was probably related to the Spanish government’s decision to minimise all healthcare activities that were not dedicated to COVID-19 in primary care centres, such as STI clinics.…”
Section: Discussionsupporting
confidence: 93%
“…As other authors have reported, this led to a reduction in the number of consultations [ 6 ] and in testing volume [ 7 ], since only patients with LGV symptoms were able to access the centres. In fact, a similar drop has been reported for a wide range of communicable diseases [ 5 ]. During this period, patients may have postponed visiting any medical centres, which may have caused more severe symptoms and additional complications in the absence of treatment [ 8 ].…”
Section: Discussionsupporting
confidence: 80%
“…In our study, the STI with lesser reduction was syphilis. This result is consistent with other data reported elsewhere, showing little increased gures and reductions of less than 10% in syphilis trends [9,14,18,20]. This may suggest that people presenting more severe clinical conditions seek medical attendance, leading to a speci c STI diagnosis [10].…”
Section: Comparison With Existing Literaturesupporting
confidence: 91%
“…A similar reduction was found for seasonal influenza in Japan [7] and tuberculosis in Jiangsu, China [8] . In the Taiwan region, the cases of notifiable infectious diseases (NIDs) decreased dramatically [9] , except for sexually transmitted diseases [10] . In contrast, Buckley et al found that social distancing led to a marked decrease in sexually transmitted diseases and foodborne infections in Spain [11] .…”
Section: Introductionmentioning
confidence: 99%